Evaluation of Some Efflux Pump Genes in Pseudomonas aeruginosa and their Relation to Antibiotic Resistance - Roaa Abd Al-rahman Abdulla; Rasmiya Abd Abo-risha (Ibn Al-Haitham Journal for Pure and Applied Sciences)
In this study, all 100 samples were collected from people suffering from burns, wounds, ear infections, blood, sputum samples, and urine from both genders. The specimens were collected from medical city hospitals during the period between September 2022 and January 2023. The results of culture and biochemical tests showed that 50 isolates were P. aeruginosa. The VITEK2 compact system confirmed the identity of 35 isolates. A VITEK2 compact system tested 35 strains of Pseudomonas aeruginosa for drug susceptibility. These strains were resistant to Cefotaxime 25 (71.43%), Ceftazidime 25 (71.43%), Cefepime 25 (71.43%), Imipenem 22 (62.86%), Meropenem 23 (65.71%), 22 (62.86%), Gentamicin 22 (62.86%), Ciprofloxacin 18 (51.43%), and Norfloxacin 21 (60%). The VITEK2 compact system used regular PCR to identify the efflux pump genes (mexT and mexF) in 35 isolates. The results indicated that mexT was positive in 20 isolates (57.1%), mexF was positive in 18 isolates (51.4%), and mexF was negative in 17 isolates (48.6%).